2004
DOI: 10.3200/jach.53.1.19-27
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship Between Protective Behaviors and Drinking Consequences Among Undergraduate College Students

Abstract: The authors identified the number, type, and frequency of protective behaviors that undergraduate college students who consume alcohol use to prevent alcohol-related consequences. Their hypothesis was that students who engage in more types of protective behaviors with greater frequency would be less likely to experience alcohol-related consequences. Participants consisted of a randomly selected sample of 1,355 undergraduates aged 18 years and older at a large public university. Students completed a mailed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
136
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 7 publications
19
136
2
Order By: Relevance
“…28,29,41 Similar to findings from Delva and colleagues (2004), we found the association between drinking strategies and the consequences of drinking was significant for females but not for males. 29 Some have suggested that due to the threat of sexual assault, females are more vigilant and aware of the need for protecting themselves. 29 Our results also revealed that females use more behaviors overall and that more behaviors used by females are associated with fewer negative consequences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…28,29,41 Similar to findings from Delva and colleagues (2004), we found the association between drinking strategies and the consequences of drinking was significant for females but not for males. 29 Some have suggested that due to the threat of sexual assault, females are more vigilant and aware of the need for protecting themselves. 29 Our results also revealed that females use more behaviors overall and that more behaviors used by females are associated with fewer negative consequences.…”
Section: Discussionsupporting
confidence: 90%
“…29 Some have suggested that due to the threat of sexual assault, females are more vigilant and aware of the need for protecting themselves. 29 Our results also revealed that females use more behaviors overall and that more behaviors used by females are associated with fewer negative consequences. However, for males, this relationship was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Convergent validity of the scale was also conducted with the same sample used to generate the factor structure, which is consistent with other studies generating protective behavioral strategy scales for alcohol (Delva et al, 2004;Martens et al, 2005Martens et al, , 2007, but items may benefit from additional convergent validity testing outside this sample. Last, we did not specify a timeframe for the use of these strategies, as we modeled the scale of the widely used PBSS for alcohol (Martens et al, 2005(Martens et al, , 2007.…”
Section: Limitationssupporting
confidence: 76%
“…eat before or during drinking, avoid drinking games, use a designated driver) and alcohol-related consequences, such that students reporting the highest use of protective behaviors also reported the lowest number of consequences (Delva et al, 2004). This association was stronger for women than for men.…”
mentioning
confidence: 95%